Effects of different combinations of radical nephroureterectomy and bladder cuff excision procedures for upper tract urothelial carcinoma on bladder recurrence - Eric Yi-Hsiu Huang; Meng-Che Tai; Hsiao-Jen Chung; Yen-Hwa Chang; William J. Huang (International Brazilian Journal of Urology, 2023)
ABSTRACT Purpose: To compare the effects of different combinations of radical nephroureterectomy (RNU) and bladder cuff excision (BCE) surgical procedures on intravesical recurrence (IVR) in patients with upper tract urothelial carcinoma (UTUC). Materials and Methods: This retrospective observational study included 452 patients who underwent RNU with BCE for UTUC between January 2010 and December 2020. The patients were classified into three groups based on different combinations of RNU and BCE surgical procedures: open RNU with open BCE (group 1, n=104), minimally invasive (MIS) RNU with open BCE (group 2, n=196), and MIS RNU with intracorporeal BCE (group 3, n=152). Data on demographics, body mass index, history, preoperative renal function, perioperative status, tumor characteristics, histopathology, and recurrence conditions were collected. Multivariate Cox regression analyses were performed to determine the impact of the surgical procedures on IVR. P-values <0.05 were considered statistically significant. Results: After a median follow-up of 29.5 months, the IVR rate was 29.6% and the IVR-free survival rate was the lowest in group 2 (group 1 vs. group 2 vs. group 3: 69.0% vs. 55.1% vs. 67.5%; log-rank P=0.048). The overall survival rate was comparable among the three groups. Multivariate analysis revealed that group 2 had a significantly higher risk of IVR than group 1 (hazard ratio=1.949, 95% confidence interval=1.082–3.511, P=0.026), while groups 1 and 3 had similar risks. Conclusions: For patients with UTUC, MIS RNU with open BCE is associated with a higher risk of IVR than open RNU with open BCE and MIS RNU with intracorporeal BCE.